Sistem Keamanan Menggunakan Kamera dan Sensor Gerak Berbasiskan Internet Of Things (IOT) - Rudy Septian; Sofyan Mufti Prasetiyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Security can be interpreted as a very important thing. Every human being needs more security as well as health. Crime cannot be separated from life, for example, theft in a warehouse is a case of theft of raw materials. The method used is to take a photo that is connected to a motion sensor that will detect any movement around. From this research, the results are in the form of a system in the form of a Smart Home tool with intelligence called the Internet of Things (IoT). The Telegram Messenger application becomes an input and notification medium in the manufacture of this system where the motion sensor will detect motion from 1-6 meters with an angle of 110° and a camera is detected, the camera will activate and take a photo of the object in 3-5 seconds.